A POSSIBILITY OF REMOTE QUALITY CONTROL OF MATERIALS: BUILDING BRICKS AS AN EXAMPLE - Ovsyanikov, V. V.; Beznosova, O. R. (Видавничий дім «Академперіодика», 2023)
Subject and Purpose. The subject of this research relates to quality parameters of substances with dielectric properties, while the main aim is development of a microwave-band remote sensing technique for measuring quality parameters of solids and loose materials.Methods and Methodology. The work is based on electromagnetic methods for determining substance quality by means of calculations and measurements of microwave signal attenuation in the substance of interest. The methods employed involve electrodynamic analysis of multilayered structures, the analytical method of moments, integral equations of diffraction theory, and objective function optimization. For a certain set of substances, preliminary calibrations and parameter storage are performed, intended for use in the determination of electromagnetic wave attenuation in the substance of interest. By comparing electromagnetic wave attenuation in the substance under testing with correspondent values shown by pre-calibrated samples, with their sets of parameters, it is possible to judge on the quality of the material under consideration.Results. By applying diffraction-theoretic methods of wave analysis in multilayered structures, the electromagnetic field attenuation in a substance (building bricks) has been calculated. The calculatеd results concerning electromagnetic signal attenuation in the test substance were compared with corresponding microwave measurements, thus permitting construction of the structural and mathematical model for the determination of the substance (building bricks) quality. The studies made it possible to evaluate the overall electrodynamic range of the measuring device, choosing the best options for the transmit and receive antenna sensors and the measuring equipment. The method of moments has been used to derive three-dimensional radiation patterns in the proximity of the device and the gain factor of the antenna sensors, wherefrom estimating the mutual electromagnetic effect that the sensors and the test substance may have on each other.Conclusion. Further development of the proposed method may imply refinement of the structural and mathematical models underlying estimation of quality parameters, determination of the overall dynamic range of the microwave-band measuring device, and provisions for automated real-time quality control and monitoring (for instance, on a conveyor), while maintaining conformance to applicable eco-standards concerning microwave intensity levels produced by the device.Keywords: quality characteristic of a substance, microwave techniques, electromagnetic wave attenuation, antenna radiation pattern, objective function optimizationREFERENCES1. Brandt, A.A., 1964. Research of dielectrics at microwave frequency. Moscow, USSR: Fizmatizd Publ. (in Russian).2. Harvey, A.F., 1965. Microwave technology. Transl. from English by V.I. Sushkevich. Vol. 1. Moscow, USSR: Sov. radio Publ. (in Russian).3. Born, M., Wolf, E., 1973. Fundamentals of optics. Transl. from English. by G.P. Motulevich. Moscow, USSR: Publ. House “Science” (in Russian).4. Brekhovskih, L.M., 1973. Waves in layered media. Moscow, USSR: Nauka Publ. (in Russian).5. Nad’, Sh.B., 1976. Dielectrometry. Transl. from Hungarian by V.V. Malov. Moscow, USSR: Energiya Publ. (in Russian).6. Viktorov, V.A., Lunkin, B.V., Sovlukov A.S., 1989. Radio wave measurements of parameters of technological processes. Moscow, USSR: Energoatomizdat (in Russian).7. Ovsyanikov, V.V., Measurements of the complex permittivity by the waveguide and resonant cavity methods. In: Proc. Int. Conf. on Actual Problems of Measuring Technique. Kyiv, Ukraine, 7—10 Sept. 1998.8. Mishchenko, S.V., Malkov, N.A., 2003. Design of radio wave (SHF) devices of nondestructive testing of materials. Tambov: Tambov State Technical University Publ. (in Russian).9. Ovsyanikov, V.V., Bukharov, S.V., Ovsyanikov, Vol.V., 2004. Method of express control of quality characteristics of substances in microwave range. Ukraine. Pat. 71301 (in Ukrainian).10. Atronenko, D.M., Gorobets, N.N., Safronova, L.P., 2006. Complex permittivity of dispersion heterogeneous system components. Visnyk of V.N. Karazin Kharkiv National University, series “Radiophysics and Electronics”, 712, pp. 10—16 (in Russian).11. Ovsyanikov, Vol.V., 2006. Quality control of bulk solids by the method of SHF scanning. In: Proc. Int. Sci. Tech. Conf. "Youth and modern problems of radio engineering and telecommunications". Sevastopol, Ukraine, 17—21 April, 2006. Sevastopol: Sevastopol State University Publ. (in Ukrainian).12. Moiseev, N.N., Ivanilov, Y.P., Stolyarova, E.M., 1978. Optimization methods. Moscow, USSR: Nauka Publ. (in Russian).13. Kuznetsov, G.V., Vypanasenko, S.I., Ovsianikov, V.V., Vovk, S.M., Gusiev O.Yu., Ovsiannikov, Vol.V., Fesak, H.I., Martynenko, S.V., 2010. Method for automated control of qualitative characteristics of substances in micro-wave range and device for its realization. Ukraine. Pat. 90540 (in Ukrainian).14. Ovsyanikov, V.V., 2010. Express control of coal quality by the radiometric method. Bull. NTUU “KPI”, series “Radio Engineering. Radio Instrument Making”, 43, pp. 24—32 (in Ukrainian).15. Bukharov, S.V., Ovsyanikov, V.V., 2011. Quality parameter diagnostics of coal and liquid oil products by electromagnetic methods, Bull. NTUU “KPI”, series “Radio Engineering. Radio Instrument Making”, 45, pp. 120—129 (in Russian).16. Suk, A.F., Sebko, V.P., Suchkov, G.M., Lazarenko, A.G., Musil, V.V., Maistrenko, A.M., 2012. Modern methods of non-destructive testing in mechanical engineering. Kharkov: NTU “KhPI” Publ. (in Russian).17. Mittra, R. ed., 1977. Computational methods for electromagnetics. Transl. from English by E.L. Burshtein. Moscow, USSR: Mir Publ. (in Russian).18. Bukharov, S.V., Ovsyanikov, V.V., 2014. Determination of quality of materials by electromagnetic methods. In: Proc. Int. Sci. Tech. Conf. “Radioengineering Fields, Signals, Devices and Systems” (RTPSAS’2014), Kyiv, Ukraine, 10—16 March 2014. Kyiv: KPI Publ. (in Russian).19. Ovsyanikov, V.V., Gorobets, M.M., Beznosova, O.R., 2020. Quality control of substances by electronic sounding in a waveguide. Bull. V.N. Karazin Kharkiv National University, series “Radiophysics and Electronics”, 32, pp. 61—70 (in Ukrainian)